CD56-Negative Extranodal Natural Killer/T-Cell Lymphoma: A Retrospective Study in 443 Patients Treated by Chemotherapy With or Without Asparaginase - Yang, Jing; Li, Pengfei; Piao, Yingshi; Liu, Xindi; Wei, Liqiang; Sang, Wei; Zhang, Luo; Wang, Liang (Frontiers in Immunology, 2022)
Objective: Extranodal natural killer/T cell lymphoma (NKTCL) is an aggressive EBV-related lymphoma, originating from NK cells or T cells. Previous study demonstrated that CD56 negative NKTCL should be recognized as a distinct subtype. In this study, the value of CD56 in NKTCL is validated in the era of asparaginase, and genomic analysis was done to dissect the differences between CD56-negative and positive NKTCL. Methods: 443 patients with newly diagnosed NKTCL were enrolled in this retrospective study, and correlation between CD56 positivity and survival outcomes was analyzed. The gene sequencing data was downloaded (http://www.biosino.org/node/project/detail/OEP000498), and bioinformatics analysis was done to delineate the tumor microenvironment and differentially expressed genes. Results: CD56 was expressed in 337 patients (76.1%). Within a median follow-up time of 51 months, the 5-year overall survival (OS) and progression free survival (PFS) rates were 63.8% and 51.9%, respectively. For the whole cohort, patients who were CD56-positive had superior OS (5-year OS, 86.2% vs. 51.9%, p=0.019) and PFS (5-year PFS, 55.9% vs. 40.1%, p=0.016). For patients in early stage disease, CD56 positivity was associated with superior OS and PFS (p=0.008 and 0.005, respectively). In patients who received non-asparaginase-based chemotherapy, CD56-negative was associated with shorter OS and PFS (p<0.001), and in patients who received asparaginase-based chemotherapy, CD56-negative was not related to inferior OS and PFS (p=0.093 and p=0.829, respectively). The genomic analysis demonstrated that CD56 positive NKTCL probably originated from NK cells and CD56 negative NKTCL originated from T cells. CD56 positive NKTCL had significantly higher proportion of resting NK cells, activated NK cells, and activated CD8+ and CD4+ T cells in the tumor microenvironment. Conclusions: CD56 negative NKTCL differs from CD56 positive NKTCL in both the tumor microenvironment and survival outcomes, and asparaginase-based treatment may overcome the poor prognosis brought by CD56 negativity.